Identification of genes related to resistance against S. Typhimurium in ovine macrophages. (February 2020) - Wang, Mengyao; Yang, Dongbing; Liu, Zhexi; Wei, Shao; Wang, Linli; Ai, Yue; Zhang, Xiaosheng; Han, Hongbing
Abstract: Salmonella enteric serovar Typhimurium ( S. Typhimurium) is a zoonotic pathogen causing public health hazards. Identification of genes related to macrophages resistance to S. Typhimurium and their immune mechanisms can provide a theoretical basis for disease resistance. In this study, sixty significant differentially expressed genes were screened between susceptible and resistant sheep macrophages by transcriptome RNA-seq. Eight significantly enriched GO terms and six canonical pathways were involved by GO and KEGG enrichment analysis. Furthermore, knockdown of HMOX1 and SLPI increased remarkably the clearance of S. typhimurium, but SPP1 had little effect on the clearance of S. Typhimurium within sheep macrophages. Altogether, these results suggest that many genes of macrophages were reprogrammed via S. Typhimurium infection, some of which may facilitate host defence against Salmonella, while others allow Salmonella to escape. Highlights: 60 DEGs related to defense against S. Typhimurium were screened in ovine macrophages. GO and KEGG enrichment analysis identified 8 significantly enriched GO terms and 6 canonical pathways. HMOX1 and SLPI might be primarily involved in the immune defense of S. T yphimurium in ovine macrophages.